Strategi Bank Syariah dalam Meningkatkan Literasi Keuangan Syariah pada Masyarakat (Studi Kasus pada BPRS Madina Mandiri Sejahtera) - Safaah Restuning Hayati (JESI (Jurnal Ekonomi Syariah Indonesia), 2018)
The research aims to find out the strategy which is conducted by BPRS Madina Mandiri Sejahtera for improving sharia financial literacy on the society, to analyse implementation of SEOJK Number 1/SEOJK.07/2014 regarding the education and improving financial literacy to the society, and to know the level of literacy on the society who had received the educational literacy program from BPRS Madina Mandiri Sejahtera. The research uses qualitative and quantitative method (mixed-method). Using of questionnaires distributed to 51 respondents. The results show that the strategy which is used BPRS Madina Mandiri Sejahtera for improving sharia financial literacy on the community is managed with through several programs such as educate and introduce product to the public using the social media, and to educate people who come to the office directly. The implementation of educational program which is conducted by BPRS Madina Mandiri Sejahtera enormously accord with the regulation SEOJK Number 1/SE.OJK.07/2014 with inclusive, systematic, measurable, accessibility, and collaboration principles. The leveling of Islamic financial literacy for the people who had obtained an educational program of literacy by BPRS Madani Mandiri Sejahtera has counted to 82.42 percent, it is the high category level.Keywords: Islamic financial literacy, BPRS, Society.